An Exploratory Study on Causes of Identity Document Theft in South Africa - Moyahabo Rakololo, William; Maluleke, Witness (International Journal of Criminology and Sociology, 2022)
This study explores the causes of Identity Document (ID) theft in South Africa, the focus is concentrated to Polokwane Central Business District (CBD), Bendor Park, and Flora Park, and the number of stores situated in the business sectors of these areas. From a quantitative standpoint, 90 respondents were selected in this study. The findings indicate that conceptual understanding of this crime (ID theft) can play a pivotal role in addressing the manifestation of this crime in a large extent as nature and extent can be established, the use of technological means also contribute to ID theft, this is also linked to individuals (victims) ignorance. For recommendations; the use of technology and conventional method in awareness can help in responding to the scale and consequence of ID theft in the Polokwane Policing Area effectively.